Services Trade Restrictiveness Index (STRI): Computer and Related Services - Nordås, Hildegunn Kyvik (OECD Trade Policy Papers, 2014)
This paper presents the services trade restrictiveness indices (STRIs) for computer services. The STRIs are composite indices taking values between zero and one, zero representing an open market and one a market completely closed to foreign services providers. The indices are calculated for 40 countries, the 34 OECD members and Brazil, China, India, Indonesia, Russia and South Africa. The STRIs capture de jure restrictions. This report presents the first vintage of indicators for computer services and captures regulations in force in 2013. The scores range between 0.08 and 0.34, with a sample average of 0.18. Explicit barriers to trade in computer services are rare, but the sector is subject to a number of economy-wide restrictions facing all sectors. Among these, restrictions on movement of people (mode 4 in GATS terminology) make the largest contribution to the index value, followed by regulatory transparency issues. The paper presents the list of measures included in the indices, the scoring and weighting system for calculating the indices and an analysis of the results